PERAN STAKEHOLDER DALAM MENJAGA KEBERSIHAN OBJEK WISATA PANTAI TIKU KECAMATAN TANJUNG MUTIARA KABUPATEN AGAM PROVINSI SUMATERA BARAT - Lespika Endang Sari; Siti Sofro Siddiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in South Nagari Tiku, Tanjung Mutiara Sub-District, Agam Regency, West Sumatera Province in order to obtain informations about the stakeholder's role in maintaining the cleanliness of Tiku Beach as tourism attraction. Some of issues in this research are (1) What is the role of stakeholders in maintaining the cleanliness in Tiku Beach as tourism attraction? (2) What are the obstacles that the stakeholders face in order to maintain the cleanliness in Tiku Beach as tourism attraction? The title of this research is "The The Role of Stakeholders in Maintaining The Cleanliness in Tiku Beach Tourism Object of Tanjung Mutiara Sub-district, Agam Regency of West Sumatera Province." This research aims to find out how the role of stakeholders in maintaining the cleanliness of Tiku Beach as a tourism object in Tanjung Mutiara Sub-District, Agam Regency, West Sumatra Province. To know the obstacles faced by stakeholders in maintaining the cleanliness of Tiku Beach in Tanjung Mutiara Sub-District, Agam Regency of West Sumatera Province, the subject of this research are the South Tiku Nagari Government, the Sadar Pesona Mutiara Putih group, the Merchants and others who take important roles in Tiku Beach, as many as 16 subjects. Datas were collected through observation, interview, and documentation. Qualitative analysis will be used to analyze the problems in this study and will be described descriptively on my paper. After the research, the results of this research is going to be about the role of stakeholders in maintaining the cleanliness of the Tiku Beach by socializing hygiene, inviting/encouraging traders to maintain the cleanliness, traders paying dues/hygiene retribution, traders clean the place of selling. While the obstacles that the stakeholders face in maintaining the cleanliness in Tiku Beach are the lack of awareness from the merchants to maintain the cleanliness of touring places and trash bins, transportations.Keywords: stakeholders, role, obstacles